Preparation method of quantum dot composite microspheres and quantum dot composite microspheres
The formation of double cladding of organic polymer and silica on the quantum dot surface through emulsification and polymerization reactions solves the problem of insufficient tolerance of quantum dot materials, significantly improves stability and is suitable for industrial applications.
Patent Information
- Application Number
- CN202411211095.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-10
AI Technical Summary
Quantum dot materials have low tolerance to water, oxygen, heat, etc., resulting in rapid attenuation of optical properties and reduced service life. The existing coating methods cannot effectively improve stability.
An emulsification and polymerization reaction method is used to form an organic polymer cladding layer on the surface of the quantum dots, and a silica cladding layer is formed thereon to achieve double cladding and enhance stability.
It significantly improves the stability of quantum dot materials, avoids the influence of external conditions such as water, oxygen, and strong blue light, extends the service life, and simplifies the coating process, which is suitable for mass production and industrial applications.
Smart Images

Figure CN119286501A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of quantum dots, and in particular, relates to a method for preparing quantum dot composite microspheres and the quantum dot composite microspheres. Background Art
[0002] As a new type of light conversion material, quantum dots have excellent optical properties such as wider excitation spectrum, narrower emission spectrum, adjustable wavelength, and high quantum yield compared to traditional organic, rare earth and other fluorescent materials. They currently have broad application prospects in many fields such as display technology, biomedicine, lighting, and energy. Display devices using quantum dots as luminescent materials have the characteristics of high brightness, high color purity, high contrast and wide color gamut, making them an ideal choice for large-panel displays and favored by major manufacturers and researchers. However, quantum dot materials often have low tolerance to water, oxygen, heat, etc., and their surface ligands may reduce luminescence performance due to chemical reactions or shedding. The application scenarios of quantum dots often require the combined action of multiple factors such as strong blue light, high temperature, water or oxygen in the air, which further leads to rapid attenuation of the optical properties of quantum dots and reduces their service life.
[0003] Among the existing main technologies, inorganic substances such as silicon dioxide are generally used to directly coat quantum dot nanoparticles, but this will reduce the luminescence performance of quantum dots and have no industrial application value; organic polymers are also used for coating, but the water and oxygen barrier effects need to be improved. Therefore, how to coat quantum dot materials, isolate quantum dots from the external environment, and improve the stability of quantum dot materials during application has become an urgent problem that needs to be solved. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one purpose of the present invention is to provide a method for preparing quantum dot composite microspheres and quantum dot composite microspheres, and quantum dot composite microspheres with good stability can be prepared by the method provided in the present application.
[0005] In the first aspect of the present invention, a method for preparing quantum dot composite microspheres is proposed. According to an embodiment of the present invention, the method includes: mixing an aqueous solution containing an emulsifier, quantum dots, a polymer monomer, a cross-linking agent and an initiator, and emulsifying to obtain a quantum dot emulsion; subjecting the quantum dot emulsion to a polymerization reaction under an inert atmosphere to form an organic polymer coating layer on at least a portion of the surface of the quantum dots to obtain organic polymer-coated quantum dot microspheres; mixing the organic polymer-coated quantum dot microspheres, a silicon source and a solvent to form a silicon dioxide coating layer on at least a portion of the surface of the organic polymer coating layer to obtain quantum dot composite microspheres.
[0006] According to the preparation method of the above embodiment of the present invention, organic polymer-coated quantum dot microspheres can be prepared by emulsification and polymerization reaction, wherein, under the action of the initiator, a chain reaction between polymer monomers can be initiated to form polymer chains, which will grow on the surface of the quantum dots and gradually completely coat the quantum dots, forming an organic polymer coating layer on the surface of the quantum dots. The cross-linking agent forms a bridge bond between the polymer chains, connecting the originally independent polymer chains together to form a three-dimensional polymer network structure, which can enhance the stability of the organic polymer coating layer, increase the density of the organic polymer, and enhance the water and oxygen barrier capacity of the organic polymer coating layer. Further utilizing the dense mesh structure and stable chemical properties of silica, a layer of silica film is formed on the outermost layer of the organic polymer-coated quantum dot microspheres, realizing the double coating of the organic polymer and inorganic oxide of the quantum dots, which can effectively avoid the influence of external conditions such as water, oxygen, and strong blue light on the quantum dots, and significantly improve the stability of the quantum dots. Thus, the method provided by the present application can prepare quantum dot composite microspheres with good stability.
[0007] In addition, the present invention can simplify the coating process of quantum dot composite microspheres, which is conducive to mass production and industrial application; the coated quantum dot composite microspheres can maintain good dispersibility in other polymer matrices, can replace diffusion particles, and can also be applied to non-barrier quantum dot films, quantum dot diffusion plates and other display fields.
[0008] In addition, the preparation method according to the above embodiment of the present invention may also have the following additional technical features:
[0009] In some embodiments of the present invention, the mass of the quantum dots accounts for 0.5% to 10% of the total mass of the polymer monomer and the crosslinking agent, thereby facilitating the production of quantum dot composite microspheres with good stability.
[0010] In some embodiments of the present invention, the mass of the crosslinking agent accounts for 10% to 60% of the mass of the polymer monomer. Thus, the crosslinking density can be precisely controlled, making the polymer network more compact, which is beneficial to improving the stability of the quantum dot composite microspheres.
[0011] In some embodiments of the present invention, the mass of the initiator accounts for 0.1% to 5% of the total mass of the polymer monomer and the crosslinking agent, thereby facilitating the acquisition of quantum dot composite microspheres with good stability.
[0012] In some embodiments of the present invention, the mass of the emulsifier accounts for 0.5% to 2.5% of the total mass of the polymer monomer and the crosslinking agent, thereby helping to form a stable emulsion system and further obtaining quantum dot composite microspheres with good stability.
[0013] In some embodiments of the present invention, the mass of the water accounts for 50% to 95% of the total mass of the quantum dot emulsion, thereby providing a sufficient continuous phase to make the emulsion more stable.
[0014] In some embodiments of the present invention, the quantum dots include oil-soluble quantum dots, which is conducive to obtaining quantum dot composite microspheres with good stability.
[0015] In some embodiments of the present invention, the polymer monomer includes at least one of styrene, methyl acrylate, methyl methacrylate, butyl acrylate, butyl methacrylate, isooctyl acrylate, isooctyl methacrylate, trifluoroethyl acrylate, trifluoroethyl methacrylate, hexafluoroisopropyl acrylate and hexafluorobutyl acrylate. This is conducive to obtaining quantum dot composite microspheres with good stability.
[0016] In some embodiments of the present invention, the crosslinking agent includes at least one of divinylbenzene, ethylene glycol diacrylate, ethylene glycol dimethacrylate, pentaerythritol triacrylate and pentaerythritol trimethacrylate. This is conducive to obtaining quantum dot composite microspheres with good stability.
[0017] In some embodiments of the present invention, the initiator includes at least one of azobisisobutyronitrile and benzoyl peroxide. This is conducive to obtaining quantum dot composite microspheres with good stability.
[0018] In some embodiments of the present invention, the emulsifier includes an oil-in-water emulsifier, which is conducive to obtaining quantum dot composite microspheres with good stability.
[0019] In some embodiments of the present invention, the emulsification time is 5 to 20 minutes, thereby ensuring that the oil phase (including quantum dots, polymer monomers, crosslinking agents and initiators, etc.) is fully mixed with the water phase (including emulsifiers), so that the oil phase can be evenly dispersed in the water phase to form a stable emulsion.
[0020] In some embodiments of the present invention, the polymerization reaction temperature is 40°C to 80°C. This ensures the effective formation of the organic polymer coating layer, further protects the quantum dots from the external environment, and improves the long-term stability of the quantum dot microspheres.
[0021] In some embodiments of the present invention, the polymerization reaction time is 24 hours to 48 hours, thereby ensuring that a stable organic polymer coating layer is formed while avoiding an adverse effect of excessive reaction time on the performance of the quantum dots themselves.
[0022] In some embodiments of the present invention, the solvent includes at least one of ethanol and water. Thus, a uniformly dispersed organic polymer-coated quantum dot microsphere dispersion can be obtained.
[0023] In some embodiments of the present invention, the solvent includes a mixture of ethanol and water. Thus, a uniformly dispersed organic polymer-coated quantum dot microsphere dispersion can be obtained.
[0024] In some embodiments of the present invention, based on the total mass of the ethanol and water, the mass of the water accounts for 5% to 15%, thereby facilitating the preparation of quantum dot composite microspheres with good stability.
[0025] In some embodiments of the present invention, the steps of mixing and reacting the quantum dot microspheres coated with organic polymers, silicon sources and solvents to form a silicon dioxide coating layer on at least part of the surface of the organic polymer coating layer to obtain quantum dot composite microspheres include: mixing the quantum dot microspheres coated with organic polymers and solvents, adjusting the pH value to alkaline, and obtaining a dispersion of quantum dot microspheres coated with organic polymers; mixing and reacting the dispersion of quantum dot microspheres coated with organic polymers and silicon sources to form a silicon dioxide coating layer on at least part of the surface of the organic polymer coating layer. This is conducive to obtaining quantum dot composite microspheres with better stability.
[0026] In some embodiments of the present invention, based on the total mass of the organic polymer-coated quantum dot microsphere dispersion, the mass of the organic polymer-coated quantum dot microsphere accounts for 0.1% to 5%, thereby facilitating the preparation of quantum dot composite microspheres with good stability.
[0027] In some embodiments of the present invention, the pH value is 8 to 11. This is conducive to obtaining quantum dot composite microspheres with good stability.
[0028] In some embodiments of the present invention, the mass ratio of the silicon source to the quantum dot microspheres coated with the organic polymer is (3-15): 1. Thus, the uniformity of the silicon dioxide coating layer can be optimized, which is beneficial to improving the stability of the quantum dot composite microspheres.
[0029] In some embodiments of the present invention, the temperature of the mixing reaction is 15° C. to 60° C. Thus, it is possible to ensure that the silicon source forms a uniform and dense coating layer on the surface of the quantum dot microspheres, thereby improving the stability and dispersibility of the quantum dot microspheres.
[0030] In some embodiments of the present invention, the mixing reaction time is 8 hours to 48 hours, thereby ensuring that the silicon source forms a uniform and dense coating layer on the surface of the quantum dot microspheres, thereby improving the stability and dispersibility of the quantum dot microspheres.
[0031] In some embodiments of the present invention, the silicon source includes tetraethyl silicate. Thus, a silicon dioxide coating layer can be formed on the surface of the quantum dot microspheres coated with the organic polymer, which is beneficial to improving the stability of the quantum dot composite microspheres.
[0032] In the second aspect of the present invention, the present invention provides a quantum dot composite microsphere, so that the quantum dot composite microsphere has good stability.
[0033] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0035] Figure 1 A scanning electron microscope image of the quantum dot composite microspheres of Example 1 of the present application is shown. DETAILED DESCRIPTION
[0036] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0037] In the first aspect of the present invention, the present invention provides a method for preparing quantum dot composite microspheres. According to an embodiment of the present invention, the method comprises:
[0038] S1. Mix and emulsify an aqueous solution containing an emulsifier, quantum dots, polymer monomers, a crosslinking agent and an initiator to obtain a quantum dot emulsion.
[0039] In this step, a quantum dot emulsion can be obtained by mixing an aqueous solution containing an emulsifier, quantum dots, polymer monomers, a cross-linking agent and an initiator, and then emulsifying the mixture. Specifically, the quantum dots, polymer monomers, a cross-linking agent and an initiator are first mixed to form an oil phase dispersion; the emulsifier and water are mixed to form an aqueous phase dispersion; and the oil phase dispersion and the aqueous phase dispersion are then mixed and emulsified. The emulsification process can effectively disperse the quantum dots in the aqueous phase solution to prevent them from agglomerating or precipitating. Among them, the emulsifier can effectively reduce the surface tension of the oil-water interface, which is conducive to the formation of emulsion droplets and the increase of new interfaces to obtain a quantum dot emulsion.
[0040] According to some specific embodiments of the present invention, the mass of the quantum dots accounts for 0.5% to 10% of the total mass of the polymer monomer and the cross-linking agent. For example, it can be 0.5%, 1%, 5%, 10%, etc. By limiting the mass proportion of quantum dots to the above range, the quantum dots can be embedded in the polymer, reducing the possibility of agglomeration between quantum dots due to interaction, which is conducive to obtaining quantum dot composite microspheres with better stability.
[0041] According to some specific embodiments of the present invention, the quantum dots include oil-soluble quantum dots. Oil-soluble quantum dots have high light stability and can maintain stable fluorescence performance under long-term illumination. The selection of oil-soluble quantum dots is conducive to obtaining quantum dot composite microspheres with good stability.
[0042] As an example, the oil-soluble quantum dots include at least one of CdS, CdSe, ZnS and ZnSe.
[0043] According to some specific embodiments of the present invention, the polymer monomer includes at least one of styrene, methyl acrylate, methyl methacrylate, butyl acrylate, butyl methacrylate, isooctyl acrylate, isooctyl methacrylate, trifluoroethyl acrylate, trifluoroethyl methacrylate, hexafluoroisopropyl acrylate and hexafluorobutyl acrylate. The above polymer monomers can undergo polymerization reaction to form an organic polymer coating layer on the surface of the quantum dot microspheres.
[0044] Furthermore, the polymer monomer includes at least one of trifluoroethyl acrylate, trifluoroethyl methacrylate, hexafluoroisopropyl acrylate and hexafluorobutyl acrylate. The above-mentioned polymer monomer contains fluorine atoms. Since the polarizability of fluorine atoms is low and the polarity of the CF bond is strong, the shared electron pairs of C and F atoms are shifted toward the fluorine atoms, forming a layer of negative charge protection around the F atom, so that negatively charged nucleophiles cannot approach to react chemically. Moreover, due to the short bond length and large bond energy of CF, the interaction force between it and active chemical substances is small, and it has high thermal and chemical stability and extremely low surface energy. Therefore, the fluorine-containing organic polymer coating layer can exert excellent water resistance and weather resistance. By selecting fluorine-containing polymer monomers, it is beneficial to the polymerization reaction while improving the water and oxygen resistance of the quantum dot microspheres coated with the organic polymer.
[0045] According to some specific embodiments of the present invention, the mass of the cross-linking agent accounts for 10% to 60% of the mass of the polymer monomer. For example, it can be 10%, 20%, 40%, 60%, etc. By limiting the mass proportion of the cross-linking agent to the above range, the cross-linking density can be accurately controlled, making the polymer network more compact, which is conducive to improving the stability of the quantum dot composite microspheres.
[0046] As an example, the cross-linking agent includes at least one of divinylbenzene, ethylene glycol diacrylate, ethylene glycol dimethacrylate, pentaerythritol triacrylate, and pentaerythritol trimethacrylate.
[0047] According to some specific embodiments of the present invention, the mass of the initiator accounts for 0.1% to 5% of the total mass of the polymer monomer and the cross-linking agent. For example, it can be 0.1%, 0.5%, 1%, 3%, 5%, etc. By limiting the mass proportion of the initiator to the above range, a chain reaction between polymer monomers can be initiated to form polymer chains, which will grow on the surface of quantum dots and gradually completely cover the quantum dots, which is conducive to obtaining quantum dot composite microspheres with better stability.
[0048] As an example, the initiator includes at least one of azobisisobutyronitrile and benzoyl peroxide.
[0049] According to some specific embodiments of the present invention, the mass of the emulsifier accounts for 0.5% to 2.5% of the total mass of the polymer monomer and the cross-linking agent. For example, it can be 0.5%, 1%, 1.5%, 2%, 2.5%, etc. By limiting the mass proportion of the emulsifier to the above range, the emulsifier can be adsorbed on the oil-water interface, reducing the interfacial tension, thereby preventing the agglomeration and precipitation of the emulsion droplets, and the emulsifier can also form a protective film to enhance the stability of the emulsion, which helps to form a stable emulsion system, and thus can obtain quantum dot composite microspheres with better stability.
[0050] According to some specific embodiments of the present invention, the emulsifier includes an oil-in-water emulsifier. The oil-in-water emulsifier can reduce the interfacial tension between the oil-water two-phase liquid, provide a stable interfacial film, and increase the viscosity of the continuous phase, thereby maintaining the stability of the emulsion, helping to prevent the aggregation and precipitation of quantum dots in the emulsion, and ensuring the uniformity and stability of the emulsion during long-term storage.
[0051] It should be noted that the oil-in-water emulsifier refers to an emulsification system in which oil is dispersed in water, with oil as the inner phase and water as the continuous outer phase.
[0052] As an example, the oil-in-water emulsifier includes, but is not limited to, at least one of cetyltrimethylammonium bromide, sodium lauryl sulfate, and polysorbate-80.
[0053] According to some specific embodiments of the present invention, based on the total mass of the quantum dot emulsion, the mass of the water accounts for 50% to 95% of the total mass of the quantum dot emulsion. For example, it can be 50%, 60%, 70%, 80%, 90%, 95%, etc. By limiting the mass of water to the above range, sufficient continuous phase can be provided to make the emulsion more stable.
[0054] According to some specific embodiments of the present invention, the emulsification time is 5 min to 20 min. For example, it can be 5 min, 10 min, 15 min, 20 min, etc. By limiting the emulsification time within the above range, it can be ensured that the oil phase (including quantum dots, polymer monomers, crosslinking agents and initiators, etc.) and the water phase (including emulsifiers) are fully mixed, so that the oil phase can be evenly dispersed in the water phase to form a stable emulsion.
[0055] It should be noted that the present invention does not specifically limit the emulsification method, and high-speed shear emulsification or ultrasonic emulsification may be used, and those skilled in the art may flexibly select the method according to needs.
[0056] S2. Under an inert atmosphere, subjecting the quantum dot emulsion to a polymerization reaction to form an organic polymer coating layer on at least a portion of the surface of the quantum dots to obtain quantum dot microspheres coated with an organic polymer.
[0057] In this step, under an inert atmosphere, the initiator in the quantum dot emulsion can initiate a chain reaction between polymer monomers to form polymer chains, which will grow on the surface of the quantum dots and gradually completely cover the quantum dots. The cross-linking agent forms bridge bonds between the polymer chains, connecting the originally independent polymer chains together, gradually forming an organic polymer coating layer on the surface of the quantum dots, and obtaining organic polymer-coated quantum dot microspheres.
[0058] According to some specific embodiments of the present invention, the gas flow rate of the inert gas is 1 mL / min to 10 mL / min. For example, it can be 1 mL / min, 3 mL / min, 5 mL / min, 7 mL / min, 10 mL / min, etc. By limiting the gas flow rate of the inert gas to the above range, it can be ensured that oxygen and moisture in the reaction system are effectively removed, and the stability of the reaction environment is maintained, which is conducive to obtaining quantum dot composite microspheres with better stability.
[0059] According to some specific embodiments of the present invention, the inert gas includes at least one of nitrogen, argon and helium. The selection of the above inert gas can effectively prevent unnecessary reaction between oxygen or other active gases and reactants during the polymerization reaction, thereby avoiding oxidation and contamination of quantum dots.
[0060] According to some specific embodiments of the present invention, the temperature of the polymerization reaction is 40°C to 80°C. For example, it can be 40°C, 50°C, 60°C, 70°C, 80°C, etc. The stability of the quantum dots can be significantly improved by forming an organic polymer coating layer on the surface of the quantum dots through the polymerization reaction. Limiting the temperature of the polymerization reaction can ensure the effective formation of the organic polymer coating layer, further protect the quantum dots from the influence of the external environment, and improve the stability of the quantum dot composite microspheres.
[0061] According to some specific embodiments of the present invention, the polymerization reaction time is 24 hours to 48 hours. For example, it can be 24 hours, 30 hours, 35 hours, 40 hours, 48 hours, etc. Limiting the polymerization reaction time can ensure that while forming a stable organic polymer coating layer, it can avoid that too long a reaction time has an adverse effect on the performance of the quantum dots themselves.
[0062] S3, mixing and reacting the quantum dot microspheres coated with the organic polymer, a silicon source and a solvent to form a silicon dioxide coating layer on at least a portion of the surface of the organic polymer coating layer to obtain quantum dot composite microspheres.
[0063] In this step, the quantum dot microspheres coated with an organic polymer, a silicon source and a solvent are mixed. During the mixing process, the silicon source will undergo a hydrolysis reaction in the solvent to generate silanols (Si-OH), and the silanols will undergo a condensation reaction to form silicon-oxygen bonds (Si-O-Si), thereby obtaining a silicon-based network structure. This network structure will be coated on the surface of the organic polymer coating layer to form a silicon dioxide coating layer to obtain quantum dot composite microspheres.
[0064] According to some specific embodiments of the present invention, step S3 further includes step S31 and step S32:
[0065] S31. Mixing the quantum dot microspheres coated with an organic polymer and a solvent, adjusting the pH value to alkaline, and obtaining a dispersion.
[0066] In this step, the quantum dot microspheres coated with organic polymers are mixed with solvents, and the quantum dot microspheres coated with organic polymers can be uniformly dispersed in the solvent. By adjusting the pH value of the mixed solution to alkaline, on the one hand, under alkaline conditions, the organic polymer coating layer will interact with the hydroxide ions in the solvent, causing the organic polymer coating layer to swell or shrink, which is beneficial to improving the dispersibility and stability of the quantum dot microspheres. On the other hand, under alkaline conditions, the hydrolysis and polycondensation reactions of the silicon source can be promoted, which is beneficial to forming a silicon dioxide coating layer on at least part of the surface of the organic polymer coating layer.
[0067] According to some specific embodiments of the present invention, the solvent includes at least one of ethanol and water. The above solvent is used to facilitate the dispersion of the organic polymer-coated quantum dot microspheres, and a uniformly dispersed organic polymer-coated quantum dot microsphere dispersion can be obtained.
[0068] According to some specific embodiments of the present invention, the solvent includes a mixture of ethanol and water. The above solvent is advantageous for dispersing the quantum dot microspheres coated with organic polymers, and a uniformly dispersed dispersion of quantum dot microspheres coated with organic polymers can be obtained.
[0069] According to some specific embodiments of the present invention, based on the total mass of the ethanol and the water, the mass proportion of the water is 5% to 15%. For example, it can be 5%, 10%, 15%, etc. By limiting the mass proportion of water to the above range, the dispersion of the quantum dot microspheres coated with organic polymers can be promoted, and a uniformly dispersed dispersion of the quantum dot microspheres coated with organic polymers can be obtained, which is conducive to obtaining quantum dot composite microspheres with good stability.
[0070] According to some specific embodiments of the present invention, based on the total mass of the dispersion, the mass proportion of the quantum dot microspheres coated with the organic polymer is 0.1% to 5%. For example, it can be 0.1%, 1%, 3%, 5%, etc. By limiting the mass proportion of the quantum dot microspheres coated with the organic polymer to the above range, the uniform coating of the inorganic oxide can be promoted, and adhesion between the microspheres can be prevented when the inorganic oxide is coated, which is conducive to obtaining quantum dot composite microspheres with better stability.
[0071] According to some specific embodiments of the present invention, the pH value is 8 to 11. For example, it can be 8, 9, 10, 11, etc. By limiting the pH value range to the above range, on the one hand, under alkaline conditions, the organic polymer coating layer will interact with the hydroxide ions in the solvent, resulting in swelling or shrinkage of the organic polymer coating layer, which is beneficial to improving the dispersibility and stability of the quantum dot microspheres. On the other hand, under alkaline conditions, the hydrolysis and polycondensation reaction of the silicon source can be promoted, which is beneficial to the formation of a silicon dioxide coating layer on at least part of the surface of the organic polymer coating layer.
[0072] S33, mixing the dispersion and the silicon source to react, forming a silicon dioxide coating layer on at least a portion of the surface of the organic polymer coating layer.
[0073] In this step, during the reaction process, when the silicon source comes into contact with water, a hydrolysis reaction can be carried out to release silanol (Si-OH) groups, and condensation reaction occurs between the silanol groups to form silicon oxygen bonds (Si-O-Si), thereby forming a silica network structure. As the hydrolysis and condensation reactions proceed, the silica network structure can be formed on the surface of the quantum dot microspheres coated with the organic polymer. The silica coating layer can enhance the stability of the quantum dot microspheres and prevent them from agglomerating or being corroded by the external environment.
[0074] According to some specific embodiments of the present invention, the mass ratio of the silicon source to the quantum dot microspheres coated with the organic polymer is (3-15): 1. For example, it can be 3: 1, 5: 1, 7: 1, 10: 1, 15: 1, etc. By limiting the mass ratio of the silicon source to the quantum dot microspheres coated with the organic polymer within the above range, the uniformity of the silicon dioxide coating layer can be optimized, which is conducive to improving the stability of the quantum dot composite microspheres.
[0075] As an example, the silicon source includes, but is not limited to, tetraethyl silicate.
[0076] According to some specific embodiments of the present invention, the temperature of the mixing reaction is 15° C. to 60° C. For example, it can be 15° C., 20° C., 40° C., 60° C., etc. By limiting the temperature of the mixing reaction to the above range, it can be ensured that the silicon source forms a uniform and dense coating layer on the surface of the quantum dot microspheres, thereby improving the stability and dispersibility of the quantum dot microspheres.
[0077] According to some specific embodiments of the present invention, the mixing reaction time is 8 hours to 48 hours. For example, it can be 8 hours, 10 hours, 20 hours, 40 hours, 48 hours, etc. By limiting the mixing reaction time within the above range, it can be ensured that the silicon source is fully hydrolyzed and condensed to form a uniform and dense coating layer, thereby improving the stability and dispersibility of the quantum dot microspheres.
[0078] In the second aspect of the present invention, the present invention proposes a quantum dot composite microsphere. According to an embodiment of the present invention, the quantum dot composite microsphere is prepared by the above method, and the quantum dots are encapsulated in a polymer matrix by coating the quantum dots with an organic polymer to form an organic polymer-coated quantum dot microsphere; further, the inorganic oxide is coated, and a layer of silicon dioxide film is formed on the outermost layer of the organic polymer-coated quantum dot microsphere by utilizing the dense network structure and stable chemical properties of silicon dioxide, so as to realize the double coating of the quantum dots with organic polymer and inorganic oxide, and effectively improve the stability of the quantum dots.
[0079] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.
[0080] Example 1
[0081] 1. 0.05 g of CdSe quantum dots, 9 g of methyl methacrylate (MMA), 1 g of ethylene glycol dimethacrylate (EGDMA), and 0.2 g of azobisisobutyronitrile (AIBN) were uniformly dispersed to prepare an oil phase dispersion; 0.15 g of hexadecyltrimethylammonium bromide was dispersed in 70 g of deionized water to prepare an aqueous phase dispersion; the above oil phase dispersion was added to the aqueous phase dispersion, and ultrasonic emulsification was performed for 10 min to prepare a quantum dot emulsion;
[0082] 2. Transfer the quantum dot emulsion to a round-bottom flask, introduce nitrogen at a flow rate of 5 mL / min, stir mechanically, and heat to 60°C to start the reaction. After 28 hours, a suspension of quantum dot microspheres coated with organic polymers was obtained. Centrifuge and wash with anhydrous ethanol three times to obtain quantum dot microspheres coated with organic polymers.
[0083] 3. The quantum dot microspheres coated with organic polymers were dispersed uniformly (solid content 1.5%) with a mixed solvent of ethanol and deionized water (ethanol: deionized water = 85:15) to obtain a dispersion of quantum dot microspheres coated with organic polymers.
[0084] 4. Transfer 100 g of the organic polymer-coated quantum dot microsphere dispersion to a round-bottom flask, stir mechanically, adjust the pH to 8 with ammonia water, add 8 g of tetraethyl silicate, react at room temperature for 24 hours, centrifuge and dry to obtain quantum dot microspheres doubly coated with organic polymer and inorganic oxide.
[0085] Example 2
[0086] The difference between Example 2 and Example 1 is that:
[0087] 1. Mix and disperse 0.05 g of CdSe quantum dots, 8 g of MMA, 2 g of EGDMA, and 0.2 g of AIBN evenly to prepare an oil phase dispersion; disperse 0.15 g of hexadecyltrimethylammonium bromide in 70 g of deionized water to prepare an aqueous phase dispersion.
[0088] Example 3
[0089] The difference between Example 3 and Example 1 is that:
[0090] 1. Mix and disperse 0.05 g of CdSe quantum dots, 6 g of MMA, 4 g of EGDMA, and 0.2 g of AIBN evenly to prepare an oil phase dispersion; disperse 0.15 g of hexadecyltrimethylammonium bromide in 70 g of deionized water to prepare an aqueous phase dispersion.
[0091] Example 4
[0092] The difference between Example 4 and Example 1 is that:
[0093] 1. Mix and disperse 0.05 g of CdSe quantum dots, 9 g of styrene (ST), 1 g of divinylbenzene (DVB), and 0.2 g of AIBN evenly to prepare an oil phase dispersion; disperse 0.15 g of hexadecyltrimethylammonium bromide in 70 g of deionized water to prepare an aqueous phase dispersion.
[0094] Example 5
[0095] The difference between Example 5 and Example 1 is that:
[0096] 1. Mix and disperse 0.05 g of CdSe quantum dots, 8 g of ST, 2 g of DVB, and 0.2 g of AIBN evenly to prepare an oil phase dispersion; disperse 0.15 g of hexadecyltrimethylammonium bromide in 70 g of deionized water to prepare an aqueous phase dispersion.
[0097] Example 6
[0098] The difference between Example 6 and Example 1 is that:
[0099] 1. Mix and disperse 0.05 g of CdSe quantum dots, 6 g of ST, 4 g of DVB, and 0.2 g of AIBN evenly to prepare an oil phase dispersion; disperse 0.15 g of hexadecyltrimethylammonium bromide in 70 g of deionized water to prepare an aqueous phase dispersion.
[0100] Example 7
[0101] The difference between Example 7 and Example 1 is that:
[0102] 1. Mix and disperse 0.5 g of CdSe quantum dots, 9 g of ST, 1 g of DVB, and 0.01 g of AIBN evenly to prepare an oil phase dispersion; disperse 0.05 g of hexadecyltrimethylammonium bromide in 70 g of deionized water to prepare an aqueous phase dispersion.
[0103] Example 8
[0104] The difference between Example 8 and Example 1 is that:
[0105] 1. Mix and disperse 0.05 g of CdSe quantum dots, 4 g of ST, 4 g of trifluoroethyl acrylate, 2 g of DVB, and 0.2 g of AIBN evenly to prepare an oil phase dispersion; disperse 0.15 g of hexadecyltrimethylammonium bromide in 70 g of deionized water to prepare an aqueous phase dispersion.
[0106] In the preparation methods of quantum dot composite microspheres of Examples 9-14, except for some experimental parameters being different from those of Example 1, the rest are the same as those of Example 1.
[0107] Some experimental parameters of the quantum dot composite microspheres of Examples 1-14 are shown in Table 1.
[0108] Table 1
[0109]
[0110]
[0111] Comparative Example 1
[0112] The difference between Comparative Example 1 and Example 1 is that:
[0113] 1. Mix and disperse 0.05 g of CdSe quantum dots, 10 g of methyl methacrylate, and 0.2 g of AIBN evenly to prepare an oil phase dispersion; disperse 0.15 g of hexadecyltrimethylammonium bromide in 70 g of deionized water to prepare an aqueous phase dispersion.
[0114] Comparative Example 2
[0115] The difference between Comparative Example 2 and Example 1 is that:
[0116] 1. Mix and disperse 0.05g CdSe quantum dots, 10g styrene, and 0.2g AIBN evenly to prepare an oil phase dispersion; disperse 0.15g hexadecyltrimethylammonium bromide in 70g deionized water to prepare an aqueous phase dispersion.
[0117] Comparative Example 3
[0118] 1. 0.05 g of CdSe quantum dots, 9 g of methyl methacrylate (MMA), 1 g of ethylene glycol dimethacrylate (EGDMA), and 0.2 g of azobisisobutyronitrile (AIBN) were uniformly dispersed to prepare an oil phase dispersion; 0.15 g of hexadecyltrimethylammonium bromide was dispersed in 70 g of deionized water to prepare an aqueous phase dispersion; the above oil phase dispersion was added to the aqueous phase dispersion, and ultrasonic emulsification was performed for 10 min to prepare a quantum dot emulsion;
[0119] 2. Transfer the quantum dot emulsion to a round-bottom flask, introduce nitrogen at a flow rate of 5 mL / min, stir mechanically, and heat to 60°C to start the reaction. After 28 hours, a suspension of quantum dot microspheres coated with organic polymers was obtained. Centrifuge and wash with anhydrous ethanol three times to obtain quantum dot microspheres coated with organic polymers.
[0120] Testing and analysis
[0121] Under the same conditions, the stability tests were performed on the quantum dot composite microspheres obtained in the above Examples 1-9 and Comparative Example 1. The specific test methods are as follows:
[0122] Stability test: The prepared quantum dot composite microspheres were added to water-based polyurethane to prepare a barrier-free quantum dot film, which was aged continuously for 500 h in a constant temperature and humidity chamber at 40 °C, 80% RH + blue light, and the brightness attenuation and color point drift were calculated at 96 h, 240 h and 500 h, respectively.
[0123] Brightness decay: Brightness decay = (initial brightness - brightness after aging) / initial brightness × 100%.
[0124] Color point drift: x(y)=|initial color coordinates-color coordinates after aging|.
[0125] The test results are shown in Table 2.
[0126] Table 2
[0127]
[0128] Combining Table 1 and Table 2, it can be seen that compared with Comparative Examples 1-3, the quantum dot composite microspheres obtained in Examples 1-14 have smaller brightness attenuation and color point drift at the same aging time, and better stability. Therefore, the stability of the quantum dot microspheres can be effectively improved after being coated with organic polymers and inorganic oxides.
[0129] Figure 1 The scanning electron microscope of the quantum dot composite microspheres obtained in Example 1 is shown. From the figure, it can be seen that the particle size of the quantum dot composite microspheres is between 0.1 μm and 1 μm, the dispersion is good, and there is no adhesion phenomenon.
[0130] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0131] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing quantum dot composite microspheres, characterized in that: include: emulsifying an aqueous solution containing an emulsifier, quantum dots, a polymer monomer, a cross-linking agent, and an initiator to obtain a quantum dot emulsion; Under an inert atmosphere, subjecting the quantum dot emulsion to a polymerization reaction to form an organic polymer coating layer on at least a portion of the surface of the quantum dots to obtain quantum dot microspheres coated with an organic polymer; The quantum dot microspheres coated with the organic polymer, a silicon source and a solvent are mixed and reacted to form a silicon dioxide coating layer on at least a part of the surface of the organic polymer coating layer to obtain quantum dot composite microspheres.
2. The preparation method according to claim 1, characterized in that: The mass of the quantum dots accounts for 0.5% to 10% of the total mass of the polymer monomer and the cross-linking agent; And / or, the mass of the cross-linking agent accounts for 10% to 60% of the mass of the polymer monomer; And / or, the mass of the initiator accounts for 0.1% to 5% of the total mass of the polymer monomer and the cross-linking agent; And / or, the mass of the emulsifier accounts for 0.5% to 2.5% of the total mass of the polymer monomer and the cross-linking agent; And / or, based on the total mass of the quantum dot emulsion, the mass of the water accounts for 50% to 95% of the total mass of the quantum dot emulsion.
3. The preparation method according to claim 1 or 2, characterized in that: The quantum dots include oil-soluble quantum dots; And / or, the polymer monomer includes at least one of styrene, methyl acrylate, methyl methacrylate, butyl acrylate, butyl methacrylate, isooctyl acrylate, isooctyl methacrylate, trifluoroethyl acrylate, trifluoroethyl methacrylate, hexafluoroisopropyl acrylate and hexafluorobutyl acrylate; and / or, the cross-linking agent comprises at least one of divinylbenzene, ethylene glycol diacrylate, ethylene glycol dimethacrylate, pentaerythritol triacrylate and pentaerythritol trimethacrylate; and / or, the initiator comprises at least one of azobisisobutyronitrile and benzoyl peroxide; And / or, the emulsifier comprises an oil-in-water emulsifier.
4. The preparation method according to claim 1 or 2, characterized in that: The emulsification time is 5 min to 20 min.
5. The preparation method according to claim 1, characterized in that: The polymerization reaction temperature is 40°C to 80°C; And / or, the polymerization reaction time is 24h to 48h.
6. The preparation method according to claim 1, characterized in that: The solvent comprises at least one of ethanol and water; And / or, the mass ratio of the silicon source to the organic polymer-coated quantum dot microspheres is (3-15):1; And / or, the temperature of the mixed reaction is 15°C to 60°C; And / or, the mixing reaction time is 8h to 48h.
7. The preparation method according to claim 1, characterized in that: The silicon source includes tetraethyl silicate; And / or, the solvent comprises a mixture of ethanol and water; And / or, based on the total mass of the ethanol and water, the mass proportion of the water is 5% to 15%.
8. The preparation method according to claim 1, characterized in that: The step of mixing the organic polymer-coated quantum dot microspheres, a silicon source and a solvent to react so as to form a silicon dioxide coating layer on at least a portion of the surface of the organic polymer coating layer to obtain quantum dot composite microspheres comprises: Mixing the quantum dot microspheres coated with the organic polymer and a solvent, and adjusting the pH value to alkaline to obtain a dispersion; The dispersion and the silicon source are mixed and reacted to form a silicon dioxide coating layer on at least a portion of the surface of the organic polymer coating layer.
9. The preparation method according to claim 8, characterized in that: The pH value is 8 to 11; And / or, based on the total mass of the dispersion, the mass proportion of the quantum dot microspheres coated with the organic polymer is 0.1% to 5%.
10. A quantum dot composite microsphere, characterized in that: The quantum dot composite microspheres are prepared by the method described in any one of claims 1-9.
Citation Information
Cited By
Preparation method of fluorinated cross-linked microsphere coated perovskite quantum dot powder
CN120059722A
Preparation method of perovskite quantum dot powder coated by fluorinated crosslinked microspheres
CN120059722B